1987
DOI: 10.1002/ajmg.1320270313
|View full text |Cite
|
Sign up to set email alerts
|

De novo X;Y translocation associated with imperforate anus and retinal pigmentary abnormalities

Abstract: Cytogenetically detectable translocations of Y chromosome material onto the distal short arm of an X chromosome are rare and result in a variable and poorly defined phenotype of short stature and short limbs occasionally associated with mental retardation. We report on a patient with a de novo 46,X,t(X;Y)(p22;q11) chromosome constitution who has additional features not previously described with this chromosome abnormality, including abnormal retinal pigmentation, imperforate anus, and hydronephrosis. Our patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…These patients have a deletion of this region, but do not have the classic MLS phenotype. Patient BA95 has imperforate anus, dysmorphic facies, retinal pigmentary abormalities, and abnormal external genitalia; however, she also has microcephaly, a feature that overlaps with the MLS spectrum of anomalies (Johnston et al, 1987). We hypothesized that 61B3-R might be part of a functional transcript, possibly spanning the telomeric breakpoints of the MLS critical region and disrupted by the deletions causing MLS.…”
Section: Cloning Of the Telomeric End Of Yac 61b3 And Conservation Ammentioning
confidence: 97%
“…These patients have a deletion of this region, but do not have the classic MLS phenotype. Patient BA95 has imperforate anus, dysmorphic facies, retinal pigmentary abormalities, and abnormal external genitalia; however, she also has microcephaly, a feature that overlaps with the MLS spectrum of anomalies (Johnston et al, 1987). We hypothesized that 61B3-R might be part of a functional transcript, possibly spanning the telomeric breakpoints of the MLS critical region and disrupted by the deletions causing MLS.…”
Section: Cloning Of the Telomeric End Of Yac 61b3 And Conservation Ammentioning
confidence: 97%
“…To our knowledge, cases subsequently reported to have the same karyotype are 4 by Wegner et al (1984), 2 by Speevak et al (1985), probable 7 by Ross et al (1985), and 1 by Johnston et al (1987). However, it is not certain whether the familial cases reported by Ross et al (1985) were the same as those reported formerly by Allderdice et al (1983).…”
Section: Discussionmentioning
confidence: 63%
“…The majority of these cases were familial (Wegner et al, 1984;Speevak et al, 1985;Ross et al, 1985;Allderdice et al, 1983;Van den Berghe et al, 1977;Tiepolo et aI., 1977;Pfeiffer, 1980;Akesson et al, 1980;Boyd et al, 1981;Yamada et al, 1982;Metaxotou et al, 1983). The number of sporadic cases was 10 (Johnston et al, 1987;Van den Berghe et al, 1977;Khudr et al, 1973;Borgaonkar et al, 1974;Bernstein et al, 1978;Hecht et al, 1980;Bernstein et al, 1980;Cohen et al, 1981 ;Zuffardi et aI., 1982).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…X/Y translocations occur rarely in the human population and some 50 cases have been reported (16)(17)(18)(19)(20)(21). The majority of these-translocations have breakpoints at Xp22 and Yq11 when analyzed cytogenetically.…”
mentioning
confidence: 99%